2006
DOI: 10.1007/bf03194632
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reliable method for DNA extraction from bivalve mantle

Abstract: A simple and reliable method was developed for extracting genomic DNA from preserved mantle tissues of Pacific oyster Crassostrea gigas for reproducible PCR amplification. The method was based on destruction of the tissue using Proteinase K, Chelex 100 resin, detergents, and urea, followed by preferential capturing of genomic DNA with silica particles. Approximately 5 mg of mantle tissue provided a sufficient quality and quantity of DNA for several hundreds of PCR reactions amplifying the hypervariable mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
(5 reference statements)
1
21
0
Order By: Relevance
“…However, we found that the modified chelex-100 protocol was the best method to extract DNA from stool. Although there are methodological differences between our study and others [32,33] , the conclusion is the same that this method is simple and efficient for PCR.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…However, we found that the modified chelex-100 protocol was the best method to extract DNA from stool. Although there are methodological differences between our study and others [32,33] , the conclusion is the same that this method is simple and efficient for PCR.…”
Section: Discussionsupporting
confidence: 45%
“…The results vary by different methods [32,33] . The use of chelex-100 has been recommended for DNA extraction in some papers, but other reports have not regarded it as being optimum because of its lowest efficiency for DNA amplification [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Deoxyribonucleic acid (DNA) extraction-Ctenophores collected at each station (Table 1) were placed individually or in groups of up to five individuals (those #1 mm) into Eppendorf tubes containing 400 mL of 4 mol L 21 urea, 1% Tween 20, 1% Nonidet P-40, 10% Chelex 100, and 0.005 mg proteinase K in sterile water (Aranishi and Okimoto 2006) within 2 h after collection. The tubes were incubated at 55uC for 20 min, and then at 105uC for 8 min.…”
Section: Methodsmentioning
confidence: 99%
“…In recent decades, researchers have been increasingly more likely to solve taxonomic problems in certain species using polymorphic genetic markers, also widely used in phylogenetic studies and population genetics (Yue and Orban, 2001;Aranishi and Okimoto, 2006). One of the most used genes is mitochondrial cytochrome oxidase I (COI), which has high phylogenetic signal and rapid evolutionary rate, which is important for characterizing populations, subspecies and species (Harrison, 1989).…”
Section: Introductionmentioning
confidence: 99%